817 Early Neonatal Outcome in Newborns Exposed to Chemotherapy During Fetal Period. (October 2012) - Fumagalli, M; Bassi, L; Scarfone, G; Peccatori, F; Pisoni, S; Passera, S; Groppo, M; Carli, A De; Sirgiovanni, I; Dessimone, F; Mosca, F
Abstract : Introduction: Cancer treatment in pregnant women is still a matter of debate as life-saving therapies for the mother and adverse effects for the fetus. Recent data support that chemotherapy from 14 wks GA onwards as safe in terms of early neonatal and long-term outcomes in children, while impaired neurodevelopmental outcome appear to be related to prematurity. Aim: To describe the early neonatal outcome in newborns exposed to chemotherapy during pregnancy. Methods: Clinical data of inborn babies, born between 2005 and 2011, from mother treated with chemotherapy, were retrospectively collected from clinical notes. Results: In our population of neonates exposed to chemotherapy during pregnancy 18% (4/22) were born between 25 and 33 weeks of GA and 73% (16/22) between 34 and 36 wks, 9% at term, (2/22). The 70% was admitted to post-natal ward and the 95% was AGA, while only 5% SGA. Neonatal complications observed were: respiratory distress syndrome 32% (7/22; 3/7 CPAP, 3/7 meccanical ventilation), hypoglycemia 23% (5/22) and jaundice 23% (5/22). Two very preterm babies (< 27 wks) developed intraventricular haemorrhage. Not cardiac complications and not significant hematological abnormalities (neutropenia, severe acute anemia and low platelet count) were observed in the neonatal period. Conclusions: According to our data chemotherapy during pregnancy doesn't seem to influence early neonatal outcome. Otherwise more studies are needed to confirm the safety of cancer treatment during pregnancy in terms of long-term cognitive and neurobehavioural outcomes in order to define treatment strategies aimed to reduce iatrogenic preterm birth.